Biology and Control of Sedges Associated with Sugarcane and Rice in Florida: SS-AGR-455/AG456, 06/2021 - Calderon, A. R.; Odero, D. C. (EDIS, 2021)
This article describes the biology and control options for sedges associated with sugarcane and rice in Florida to assist growers in making correct identification and appropriate management decisions to help control these species. Written by A. R. Calderon and D. C. Odero, and published by the UF/IFAS Agronomy Department, June 2021.